Randomised controlled trial of a synthetic triglyceride milk formula for preterm infants. Issue 3 (1st November 1997) - Lucas, A; Quinlan, P; Abrams, S; Ryan, S; Meah, S; Lucas, P J
Abstract : AIMS: To test whether use of infant formula containing synthetic structured triglycerides results in: (i) increased palmitate absorption; (ii) increased total fat absorption; (iii) reduction in calcium soap formation in the gut; and hence (iv) increased calcium absorption. METHODS: A randomised study was made of 24 infants comparing three formulas, one containing the synthetic fat Betapol with 74% of palmitate in the 2-position, which was substantially higher than in the two comparison diets (8.4% and 28%). The hypothesised outcomes were tested using balance studies, detailed chemical analysis of stool specimens and dual calcium isotope tracers ( 44 calcium orally and 46 calcium intravenously). RESULTS: Three of the four hypotheses were confirmed: use of a formula rich in 2-position palmitate (i) improved palmitate (16:0) and also (18:0) absorption; (ii) reduced the formation of insoluble calcium soaps in the stool; and (iii) improved calcium absorption, determined by the dual tracer technique from 42 (SE 3)% to 57 (7)%. CONCLUSION: Synthetic triglycerides that mimic the stereoisometric structure of those in breast milk may have a valuable role in the design of formulas used for preterm infants in neonatal intensive care units.